Defect engineering toward strong photocatalysis of Nb-doped anatase TiO2: Computational predictions and experimental verifications - Khan, Sovann; Cho, Haneol; Kim, Donghun; Han, Sang Soo; Lee, Kyu Hwan; Cho, So-Hye; Song, Taeseup; Choi, Heechae (ELSEVIER, 2017)
Understanding the roles of point defects in optical transitions is a key to the desirable engineering of photochemical materials. In this study, the origins of the significantly varying optical and photochemical properties of Nb-doped anatase TiO2 were systematically investigated, using density functional theory (DFT) calculations and experimental verifications. We found from DFT calculations that the desirable band gap reduction of anatase TiO2 by similar to 0.1 eV reported in many of experimental reports and the resultant improvements of photocatalytic and photovoltaic efficiencies of Nb5+-doped anatase TiO2 are due to the formation of complex (Nb-T1-V-Ti)(3)- as the compensator of Nb-Ti(+). Our experiments demonstrated that the O-2-rich annealing, which is expected to increase the concentration of desirable (Nb-TI-V-Ti)(3-) complex, narrows band gap of TiO2 and strongly enhances the photocatalytic activity of Nb-doped TiO2 particle. On the contrary, pure TiO2 showed rather worse photocatalytic performances when annealed in O-2 rich atmosphere, which is due to the formation of deep level by O-interstitial defect (O-1). Theoretically obtained charge effective masses could further explain the different photocatalytic activities of undoped and Nb-doped TiO2. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 1ST-PRINCIPLES CALCULATIONS; RAMAN-SPECTRA; EXCHANGE; TUNGSTEN; ENERGY; WATER